From Inca to indigenous: Change in the symbolism of the sun in the early 19th century - Sala i Vila, Nuria (1990)
The historian Manuel Burga has analyzed in a recent book the historical roots of the revolution of indigenous mentalities that gave way to the formulation of an Andean utopia. In it he highlights the notable role played in all of this by festivals, masquerades, theater and ritual performances. It also highlights how in these manifestations of said utopian ideal a distinction is generally observed: while in the towns it was embodied by the annual ritual festival of the death of the Inca Atahuallpa in Cajamarca, in the cities it appears in the parades of the nobles dressed with the Inca attributes and clothing.